2013 10th IEEE International Conference and Workshops on Automatic Face and Gesture Recognition (FG) 2013
DOI: 10.1109/fg.2013.6553818
|View full text |Cite
|
Sign up to set email alerts
|

Compensating inaccurate annotations to train 3D facial landmark localization models

Abstract: Abstract-In this paper we investigate the impact of inconsistency in manual annotations when they are used to train automatic models for 3D facial landmark localization. We start by showing that it is possible to objectively measure the consistency of annotations in a database, provided that it contains replicates (i.e. repeated scans from the same person). Applying such measure to the widely used FRGC database we find that manual annotations currently available are suboptimal and can strongly impair the accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The ground truth displacements are only used during training to derive the templates and are specific to each descriptor. We have shown that this strategy is more accurate than simply trusting the manual annotations [57].…”
Section: B Geometric Descriptorsmentioning
confidence: 91%
See 2 more Smart Citations
“…The ground truth displacements are only used during training to derive the templates and are specific to each descriptor. We have shown that this strategy is more accurate than simply trusting the manual annotations [57].…”
Section: B Geometric Descriptorsmentioning
confidence: 91%
“…In all cases, we obtained descriptor templates for each landmark by averaging over the training set. As manual annotations for FRGC have been shown to be rather noisy, we used the least squared corrections of uncertainty algorithm [57] to build the templates. In brief, this means that we assumed an uncertainty in the manual annotations, which were allowed to move within a small neighborhood of radius r u to enforce consistency of the extracted descriptors.…”
Section: B Geometric Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation